Предмет: Алгебра,
автор: zheny2123
Решите уравнение (х-11)(-х+9)=0
Ответы
Автор ответа:
0
-х²+9х+11х-99=0
-х²+20х-99=0 :1
х²-20х+99=0
Д=(-20)²-4*1*99=400-396=4
х1=(20+2) ÷ 2*1= 22÷2=11
х2=(20-2) ÷ 2*1= 18÷2=9
-х²+20х-99=0 :1
х²-20х+99=0
Д=(-20)²-4*1*99=400-396=4
х1=(20+2) ÷ 2*1= 22÷2=11
х2=(20-2) ÷ 2*1= 18÷2=9
Похожие вопросы
Предмет: Математика,
автор: arseniyzhelnin
Предмет: Алгебра,
автор: nelinail74
Предмет: Математика,
автор: svetabashkirovaa
Предмет: Алгебра,
автор: klimenkol21
Предмет: Математика,
автор: Timohkanovaana